Meaningful Work Protects Judges with Occupational Stress, Secondary Traumatic Stress, and Burnout: (A Study of Indonesian Judges of The Supreme Court of the Republic of Indonesia) - Mirza, Mochamad; Parahyanti, Endang (Jurnal Hukum dan Peradilan, 2025)
Studies have shown that daily job demands encountered by judges' might result in stress. Continuous stress can affect judges personal lives and job performance. However, several judges experience stress differently due to many factors affecting stress levels. Previous research suggested that meaningful work might mitigate the adverse impacts of the negative effects of stress. This study investigated occupational stress, secondary traumatic stress, and burnout among Indonesian judges and their relationship to meaningful work. This research involved a convenience sample of 2,839 judges in Indonesia. The findings revealed a significant negative correlation between occupational stress, secondary traumatic stress, burnout, and meaningful work, with burnout being identified as the most potent negative predictor. This study also found that judges had moderately low levels of occupational stress, low levels of secondary traumatic stress, low levels of burnout, and high levels of meaningful work. Based on these findings, it is recommended that institutions implement psychological support systems to enhance judges’ sense of meaningful work, thereby minimizing the detrimental effects of occupational stress.